Dynamic precipitation in Mg-3Al-1Zn alloy during different plastic deformation modes. (1st September 2016) - Dogan, E.; Wang, S.; Vaughan, M.W.; Karaman, I.
Abstract: Various AZ31 Mg alloy samples were either Equal Channel Angular Extrusion Processed (ECAP) or uniaxial tensile tested at 150 °C and 200 °C to study dynamic precipitation in this alloy. The microstructures of both the ECAP and tension specimens were investigated in detail. Scanning Electron Microscopy, Transmission Electron Microscopy (TEM), and Scanning TEM (STEM) studies demonstrated the presence of a new phase, called ɸ′, in the dynamically recrystallized (DRX) regions. The precipitate composition was determined to be approximately Mg75 (AlZn)25  wt.%. (Mg82 (AlZn)18  at.%). Since these precipitates were not observed in the initial, non-deformed samples, even after exposing them to heat treatments at 150 °C for 200 h, they were concluded to be a consequence of the plastic deformation during ECAP or tensile testing. The ɸ′ particles, which mostly form along the grain boundaries of the DRX grains, absorb solute solution hardening elements Al and Zn from the surrounding DRX grains, which consequently consist primarily of Mg. The resulting DRX grains therefore seem to be compositionally softer, promoting deformation localization and eventual macroscopic failure, thus offering a rationale for why ECAP and tension samples tend to fail along DRX regions. Graphical abstract: